2017
DOI: 10.1017/s1463423617000706
|View full text |Cite
|
Sign up to set email alerts
|

A realist evaluation of social prescribing: an exploration into the context and mechanisms underpinning a pathway linking primary care with the voluntary sector

Abstract: This article adopts a realist approach to evaluate a social prescribing pilot in the areas of Hackney and City in London (United Kingdom). It unpacks the contextual factors and mechanisms that influenced the development of this pilot for the benefits of GPs, commissioners and practitioners, and reflects on the realist approach to evaluation as a tool for the evaluation of health interventions. Primary care faces considerable challenges including the increase in long-term conditions, GP consultation rates, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
194
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(199 citation statements)
references
References 28 publications
4
194
0
1
Order By: Relevance
“…Our findings confirm the importance of primary‐care practitioners’ engagement with social prescribing (White, Kinsella, & South, )(Whitelaw et al., ). In common with other studies (Bertotti et al., ; Brandling & House, ; Mercer et al., ), we find that link workers’ experiences of primary‐care engagement with social prescribing indicate that practitioners can be both slow to identify patients who may benefit from social prescribing and to refer. We identify as an additional issue the referral of patients with severe and complex social problems who may be unable to engage with social prescribing.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our findings confirm the importance of primary‐care practitioners’ engagement with social prescribing (White, Kinsella, & South, )(Whitelaw et al., ). In common with other studies (Bertotti et al., ; Brandling & House, ; Mercer et al., ), we find that link workers’ experiences of primary‐care engagement with social prescribing indicate that practitioners can be both slow to identify patients who may benefit from social prescribing and to refer. We identify as an additional issue the referral of patients with severe and complex social problems who may be unable to engage with social prescribing.…”
Section: Discussionsupporting
confidence: 88%
“…Bertotti et al. () and Skivington, Smith, Chng, Mackenzie, and Wyke () identified the lack of availability of suitable onward referral services as a barrier to social prescribing. These deficiencies were frequently highlighted by link workers in both phases of this study, who identified that “a massive barrier is other services’ capacities” (P1, Interview, Phase 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, no previous systematic synthesis of existing literature, using a realist lens, has explored how this role can be implemented optimally. Other reviews have looked more at clinical navigation, rather than the use of local assets to address social determinants of health [34,35], have not adopted a realist lens when working with data [36][37][38] or have not focused specially on connector schemes [39]. A realist review that explored social prescribing more broadly described link workers as essential but not enough, on their own, to ensure that desired outcomes are achieved [15]; other elements, as touched on in our review, need to be in place, such as a vibrant VCS, changing the medical model focus in some health settings, and a shift in the mindset of patients.…”
Section: Discussionmentioning
confidence: 99%